2021
DOI: 10.3390/ijms222212535
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-1 Facilitates Transmesothelial Water Permeability: In Vitro and Ex Vivo Evidence and Possible Implications in Peritoneal Dialysis

Abstract: We previously showed that mesothelial cells in human peritoneum express the water channel aquaporin 1 (AQP1) at the plasma membrane, suggesting that, although in a non-physiological context, it may facilitate osmotic water exchange during peritoneal dialysis (PD). According to the three-pore model that predicts the transport of water during PD, the endothelium of peritoneal capillaries is the major limiting barrier to water transport across peritoneum, assuming the functional role of the mesothelium, as a semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Nonspecific binding sites were blocked with 1% bovine serum albumin in PBS for 30 min. Sections were then incubated with the primary antibodies rabbit anti-BAR3 (SC-50436, Santa Cruz Biotechnology, Inc., www.scbt.com, accessed on 22 November 2022) with mouse anti-AQP2 antibody [38] (SC-515770, Santa Cruz Biotechnology, Inc., www.scbt.com, accessed on 22 November 2022) or mouse anti-NKCC2 [20] or mouse anti-AQP1 [39,40] (SC-25287, Santa Cruz Biotechnology, Inc., www.scbt.com, accessed on 22 November 2022). Sections were incubated with Alexa Fluor-conjugated secondary antibody.…”
Section: Human Kidney Immunofluorescencementioning
confidence: 99%
“…Nonspecific binding sites were blocked with 1% bovine serum albumin in PBS for 30 min. Sections were then incubated with the primary antibodies rabbit anti-BAR3 (SC-50436, Santa Cruz Biotechnology, Inc., www.scbt.com, accessed on 22 November 2022) with mouse anti-AQP2 antibody [38] (SC-515770, Santa Cruz Biotechnology, Inc., www.scbt.com, accessed on 22 November 2022) or mouse anti-NKCC2 [20] or mouse anti-AQP1 [39,40] (SC-25287, Santa Cruz Biotechnology, Inc., www.scbt.com, accessed on 22 November 2022). Sections were incubated with Alexa Fluor-conjugated secondary antibody.…”
Section: Human Kidney Immunofluorescencementioning
confidence: 99%
“…The short circuit current (Isc) and the transepithelial resistance (Rt) were measured as previously described [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…All these above-mentioned changes in peritoneum permeability are thought to result from the impairment of free water transport and ultrafiltration abilities due to defected water channel protein, aquaporin 1 (AQP1) on both endothelium and mesothelium upon the occurrence of peritoneum fibrosis [15,16]; moreover, Piccapane et al showed functional AQP1 was crucial for transmesothelial water transport. Another study also demonstrated that AQP1-containing exosomes present in peritoneal dialysis effluent may potentially serve as a biomarker for the integrity of the peritoneum, and reflect the water permeability status of the peritoneum; more importantly, detection of those AQP1-containing exosomes may be used to predict ultrafiltration failure in PD patients [17][18][19]; however, although the changes shown on PET and impairment of AQP1 were considered as relevant indications to fibrosis and angiogenesis, the underlying mechanism of these functional changes on peritoneum remains to be elucidated [20][21][22][23].…”
Section: Introductionmentioning
confidence: 98%